Racial heteroidentification: the context of affirmative actions in Higher Education (Práxis Educativa, 2022)
The objective of this paper was to understand how the Universidade Federal de Juiz de Fora (UFJF), the Universidade Federal de Minas Gerais (UFMG) e the Universidade Federal de Ouro Preto (UFOP), located  in the state of Minas Gerais, Brazil, are building mechanisms of racial heteroidentification to accompany the implementation of Law no. 12.711/2012. In order to do that, a comparative analysis was carried out through documentary research and with contributions of the literature of racial studies. In this plot, it was possible to perceive that the strategies developed in these universities contribute to the formation of a social diversity that breaks with the hegemony of whites in school spaces. In this way, it was observed that the practices developed help subjects to self-identify, which can work as an anti-racist tool, capable of denaturalizing the absences and exclusions of black bodies in the academic scenario.Keywords: Universities. Affirmative policies. Racial heteroidentification.